Analysis on the perception and socio-demographic factors influencing the top-of-mind awareness and urgent environmental issues - Viray, Gayzcee (Animo Repository, 2022)
The perception of a person as well as the socio-demographic factors such as age, residence and educational attainment influence the top-of-mind awareness (TOMA) and the top urgent environmental issues. The dataset of the Perceptions on Philippine Conservation 2021 Activity Report was analyzed using descriptive analysis. Based on the analysis conducted, pollution ranked as the leading top-of-mind environmental issue. The highest number of responses for pollution came from the National Capital Region (NCR). It was also observed that some local perceptions of the community were different from TOMA and actual status of the region. Furthermore, the highest response on pollution and climate change, as the top urgent environmental issues, came from age group 19-40 years old. Socio-demographic factors affect the community’s awareness.